(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This article discusses the role of pragmatics in teacher speech within classroom settings, examining how teachers use language not just for instruction, but for managing classroom dynamics, encouraging participation, and fostering positive learning environments. Five core areas are identified and analyzed: speech acts, politeness strategies, discourse management, pragmatic failures, and the importance of pragmatic competence in teacher training.